2008
DOI: 10.1158/0008-5472.can-08-2895
|View full text |Cite
|
Sign up to set email alerts
|

K-ras and Wnt Signaling Synergize to Accelerate Prostate Tumorigenesis in the Mouse

Abstract: Aberrant Ras and Wnt signaling are emerging as key events in the multistep nature of prostate tumorigenesis and progression. Here, we report the generation of a compound model of prostate cancer to define the synergism of activated K-ras (K-ras +/V12 ) and dominant stabilized B-catenin (Catnb +/lox(ex3) ) in the murine prostate. Recombination of floxed alleles and subsequent expression of oncogenic transgenes was mediated by Cre recombinase expression governed by the composite Probasin (PB) promoter (termed PB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 45 publications
(64 reference statements)
9
66
0
Order By: Relevance
“…Moreover, STI-571 (Glivec), a tyrosine kinase inhibitor, downregulates the b-catenin-signaling activity and suppresses cell proliferation (46). Finally, additional studies showed that RAS pathway activation can strongly cooperate with Wnt signaling to drive development of several type of carcinoma in vivo (47,48), and that PI3K/AKT pathway can regulate Wnt signaling in various cancers (49). Our study emphasizes the potential cooperative link between Wnt pathway and RAS/MAPK and PI3K/AKT signaling pathways in NF1-associated tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, STI-571 (Glivec), a tyrosine kinase inhibitor, downregulates the b-catenin-signaling activity and suppresses cell proliferation (46). Finally, additional studies showed that RAS pathway activation can strongly cooperate with Wnt signaling to drive development of several type of carcinoma in vivo (47,48), and that PI3K/AKT pathway can regulate Wnt signaling in various cancers (49). Our study emphasizes the potential cooperative link between Wnt pathway and RAS/MAPK and PI3K/AKT signaling pathways in NF1-associated tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies have reported abnormal expression and mutation of b-catenin in PCa and in other solid cancers (Yardy & Brewster 2005). Synchronous activation of K-ras and b-catenin significantly reduced survival in a mouse model, associated with accelerated tumorigenesis and the development of invasive carcinoma (Pearson et al 2009). In addition, Wnt/b-catenin activation promoted PCa progression in another mouse model (Yu et al 2010), and the small molecule inhibitor of Wnt/b-catenin signaling, PKF118-310, has recently been shown to inhibit the proliferation of PCa cells (Lu et al 2009).…”
Section: Foxo3amentioning
confidence: 99%
“…In mouse models with the SV40 large T-antigen, which inactivates p53 and Rb [126], or in mice expressing mutated K-ras and form invasive carcinoma [127], or in mice with loss of PTEN expression [128], β-catenin overexpression can promote highly invasive prostate cancer and squamous metaplasia, even in the absence of androgens. These findings provided strong evidence for a critical role of the Wnt/β-catenin signaling in prostate cancer development and progression.…”
Section: Wnt Signaling In Disease Models Of Crpcmentioning
confidence: 99%